2021
DOI: 10.1111/jpc.15406
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement initiative to improve the duration of kangaroo mother care for twin preterm neonates born at a tertiary care hospital in resource‐limited settings

Abstract: Aim Kangaroo mother care (KMC) can be challenging in multiple births and more so in resource‐limited settings. This study aims at increasing the mean duration of KMC with early initiation in twin preterm neonates born at a tertiary care hospital using a quality improvement (QI) initiative. Methods Barriers for poor KMC practice in twin preterm neonates born at the tertiary care hospital were analysed and baseline data were collected over a period of 4 months using a predesigned proforma. A QI team was formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…These studies have tested various interventions such as awareness of staff and parents, foster KMC, simpler KMC documentation, increasing resources such as KMC chairs and provision of bed to mother, rewarding staff and parents sequentially. [14][15][16][17][18][19] Either supervision or high intensity training (>5 days training combined with >1 interactive method) alone or even in combination is unable to bring greater changes in quality care. While low intensity training combined with QI collaborative has a greater impact on improving quality care in low-income and middleincome countries.…”
Section: Available Knowledge and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…These studies have tested various interventions such as awareness of staff and parents, foster KMC, simpler KMC documentation, increasing resources such as KMC chairs and provision of bed to mother, rewarding staff and parents sequentially. [14][15][16][17][18][19] Either supervision or high intensity training (>5 days training combined with >1 interactive method) alone or even in combination is unable to bring greater changes in quality care. While low intensity training combined with QI collaborative has a greater impact on improving quality care in low-income and middleincome countries.…”
Section: Available Knowledge and Rationalementioning
confidence: 99%
“…These QI initiatives have implemented KMC ranging from 2 months to 9 months. These studies have tested various interventions such as awareness of staff and parents, foster KMC, simpler KMC documentation, increasing resources such as KMC chairs and provision of bed to mother, rewarding staff and parents sequentially 14–19…”
Section: Introductionmentioning
confidence: 99%
“…A program aimed to increase the practice of KC for twins born at tertiary care hospitals, known as the quality improvement (QI) project, was undertaken by researchers in Bengaluru, India (Arora et al, 2021). (Tertiary hospitals offer specialized treatment at a high level of care; Torrey, 2021).…”
Section: Twin Researchmentioning
confidence: 99%
“…While the first study suggested that the duration of KMC improved [5], the second study also suggested an improvement in the timing of initiation of KMC. The average day of initiation of KMC improved from 8th to 3rd day of life [6].…”
mentioning
confidence: 96%
“…Two recent studies suggested an improvement in KMC duration [5,6] through a quality improvement (QI) approach in a tertiary-care neonatal unit. A QI team was formed, solutions were prioritised through focus group discussions and implemented through Plan-Do-Study-Act (PDSA) cycles.…”
mentioning
confidence: 99%